Entrepreneurial Framing: How Category Dynamics Shape the Effectiveness of Linguistic Frames - Taeuscher, Karl; Rothe, Hannes (Strategic Management Journal, 2024)
How do new entrepreneurial ventures effectively deploy linguistic frames to attract customer demand? Drawing on framing and categories research, we develop and test theory about how category dynamics shape the effectiveness of two commonly observed frames—social impact framing and innovativeness framing—in the context of prosocial categories. We test our predictions by tracking entrepreneurial ventures in the market category for massive open online courses over the category's first 10 years of existence (2012–2021). Our fixed-effects models show that higher levels of category salience increase the effectiveness of a social impact framing but decrease the effectiveness of an innovativeness framing; conversely, higher levels of category crowdedness decrease the effectiveness of a social impact framing but increase the effectiveness of an innovativeness framing.